CHARACTERISTICS OF PERSONAL PSYCHOLOGICAL PROTECTION IN EXTREME SITUATIONS (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
The article describes the specific features of psychological protection of a person in extreme situations, analyzed them from a psychological point of view and gave their descriptions. Also, the dynamics of the extreme situation and its uniqueness were fully studied.